(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Vasti is one among the most widely used therapeutic procedures in Ayurveda especially in neurological and degenerative diseases. Proper guidelines for Panchakarma procedures are laid out in the classics for better outcome and minimal complications. Till date, the guidelines hold value and current practices revolve around the same. Though there are plenty of insights into the benefits of Vasti, minimal information is available about the complications and management. This case report is an attempt to understand how the administration of a Kashaya vasti in a known case of lumbar spondylosis resulted in complication and managed with oral administration of Kamadudharasa. A 64 year old male patient with primary complaint of low back ache developed pain and burning sensation per abdomen after giving Erandamooladi niruhavasti. He went to a state of confusion. Initial management was done using Dhanvantaram gutika, which failed to revive the patient. A single dose of Kamadudha rasa was administered sublingually following which he regained consciousness. This was followed by a reduction in the burning sensation and the patient felt better. On detailed analysis, it was found that the patient had a history of gastritis and was on medication for the same. The Teekshna guna of Erandamuladi vasti probably worsened the state of Pitta in his Koshta and lead to the complications such as Sula, Daha and Moha. A detailed understanding of the selection of the right type of Niruha vasti is necessary for better outcomes. This brings our attention to the importance of Sameekshya bhava and how it plays an important role in deciding the outcome of Panchakarma procedures. Failure to do so may result in Vyapath/complications.